THE NEED OF INTERACTIVE CD MEDIA DEVELOPMENT BASED ON CHARACTER IN COURSE OF DEVELOPMENT OF PARTICIPANTS IN HIGHER EDUCATION - Yasmi, Fifi; Hutabri, Elbert; Asril, Asril (Jurnal Pendidikan dan Pengajaran, 2017)
Media is a tool needed in learning activities that aim to help learners more easily understand the subject matter. This study aims to find out how important media interactive CD-based character in the course Development of Learners. This research uses the descriptive method with the instrument in the form of a questionnaire given to students who follow the recovery of the students' progress. Based on the results of the study 81.25% of respondents stated that they have never seen a character-based interactive CD media in the course of the development of learners. They suggested that the making of character-based interactive CD because with the media is expected subject matter more easily understood. So far, the media are still in the form of power points and textbooks so that learning activities are less interesting. From the results of this study suggested to the lecturers in order to create a more interactive media such as character-based interactive CD for the course of the development of learners.